Electrode catalyst coated with phosphonium type ion liquid and fuel cell using the same
Patent Information
- Application Number
- JP2023139387
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2025-03-13
AI Technical Summary
【0010】 本発明のホスホニウム型イオン液体コーティングされた電極触媒では、従来のペルフルオロスルホン酸系カチオン交換膜がコーティングされた電極触媒と比較しても安価なコストで製造できる可能性がありつつ、水素の変換効率や耐久性の面でも同等以上の性能を発揮する。加えてFCセルとして軽量化が図れるので、FCスタックとしても軽量化を図れたり、同重量のFCスタックを搭載するとしても、より多くのFCセルから構成することができるので、高出力のFCスタックとしたりすることもできる。
Smart Images

Figure 2025033586000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a catalyst electrode coated with a phosphonium-type ionic liquid for use in fuel cells and the like. [Background technology]
[0002] In recent years, as carbon dioxide is considered to be one of the causes of global warming, attention has been focused on fuel cells, which do not emit carbon dioxide during use. Fuel cells include solid polymer fuel cells as a power source for individual households, phosphoric acid fuel cells as a power source for factories and buildings, and automobiles powered by fuel cells (FCV: Fuel Cell Vehicle). However, further development of FC stacks is necessary for their widespread use, and research into this is being actively conducted around the world.
[0003] A fuel cell is a power generation device that generates electricity directly by chemically reacting hydrogen and oxygen. On the anode side of a fuel cell, hydrogen is reacted with a catalyst to extract electrons and produce protons (H + Meanwhile, on the cathode side, the protons that have passed through the electrolyte and the supplied oxygen cause an oxygen reduction reaction with the electrons supplied from the cathode electrode and an electrode catalyst to produce water, which is then discharged outside the system.
[0004] The electrolyte near the electrode catalyst of the cathode electrode must be able to block the intrusion of hydrogen, while allowing protons and oxygen to pass through and contact the catalyst, and must also be able to quickly discharge the water generated by the redox reaction. Under these conditions, the cathode side typically uses an electrode catalyst with a catalyst supported on the electrode, and the surface of the electrode is generally coated with a perfluorosulfonic acid cation exchange membrane, the product name of which is "Nafion" (a registered trademark of The Chemours Company FC Limited Liability Company).
[0005] FCVs for small and medium-sized vehicles have been put into practical use and have reached the stage of widespread use. However, when considering the application of FCVs to large vehicles such as large buses and large trucks, the amount of electricity required for driving will be greater than that of small and medium-sized vehicles, and the amount of hydrogen consumed will inevitably increase. On the other hand, it is known that perfluorosulfonic acid-based cation exchange membranes inhibit the oxygen reduction reaction due to the inhibition of oxygen transport and the poisoning of the catalyst surface derived from sulfonic acid groups, and with the conventional cathode side electrode catalyst configuration, there is a risk that the coating of the perfluorosulfonic acid-based cation exchange membrane will deteriorate with this increase in hydrogen consumption. In addition, the increase in water produced by the oxygen reduction reaction may cause a catalyst surface reaction, which may impair the durability of the electrode or reduce the reaction efficiency with oxygen. In addition, perfluorosulfonic acid-based electrolyte membranes are expensive due to the complex synthetic raw materials and manufacturing process, and their heat resistance is not sufficient.
[0006] Recently, various kinds of ionic liquids have been developed as materials that have the property of conducting electricity, and their use as materials for electronic devices has been considered. Ionic liquids are liquids that have ionic conductivity and consist only of ions in the atmosphere, and have characteristics such as a wide liquid temperature range, low volatility, flame retardancy, and high electrochemical stability. For example, Patent Document 1 discloses a technology that uses a phosphonium ionic liquid as an electrolyte for electronic devices. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Special table number 2016-507855 Summary of the Invention [Problem to be solved by the invention]
[0008] The problem that this invention aims to solve is to find an ionic liquid that has high conversion efficiency and highly durable coating properties, and can be used to replace the perfluorosulfonic acid-based cation exchange membrane, which is the coating material for the cathode electrode catalyst, even in the FC stacks of large vehicles. [Means for solving the problem]
[0009] The most important feature of the electrode catalyst of the present invention is that it is coated with a phosphonium-type ionic liquid or a phosphonium-type ionic compound represented by the following chemical formula 1. P + (C8H 17 )3R1X - (chemical formula 1) In the chemical formula 1, C8H 17 is a linear octyl group, R1 is a linear or branched alkyl group having 1 to 18 carbon atoms, or an alicyclic alkyl group having 1 to 18 carbon atoms, and X - is the anion component. Effect of the Invention
[0010] The phosphonium-type ionic liquid-coated electrode catalyst of the present invention can be manufactured at a lower cost than conventional electrode catalysts coated with perfluorosulfonic acid-based cation exchange membranes, and exhibits equal or better performance in terms of hydrogen conversion efficiency and durability. In addition, the weight of the FC cell can be reduced, so the weight of the FC stack can also be reduced, and even if an FC stack of the same weight is installed, it can be composed of more FC cells, so it can be made into a high-output FC stack.
[0011] Furthermore, since the phosphonium-type ionic liquid of formula 1 used in the coating of the present invention is highly hydrophobic, the water generated in the oxygen reduction reaction is quickly removed from the electrode catalyst surface, thereby suppressing the deterioration of the catalytic function. [Brief description of the drawings]
[0012] [Figure 1]FIG. 1 is an explanatory diagram showing a schematic structure of an electrode catalyst coated with an ionic liquid according to the present invention. [Diagram 2] FIG. 1 is an explanatory diagram showing a schematic diagram of a cathode electrode provided with an electrode catalyst according to the present invention. [Diagram 3] An explanatory diagram showing an overview of an FC cell equipped with the electrodes of the present invention. [Figure 4] Comparison of mass activity and surface area specific activity bar graph 1 [Diagram 5] Comparison of mass activity and surface area specific activity bar graph 2 [Figure 6] Comparison graph 1 of test cycle number and Pt surface area retention rate [Figure 7] Comparison graph of test cycle number and Pt surface area retention rate BEST MODE FOR CARRYING OUT THEINVENTION
[0013] Hereinafter, the present invention will be described in detail with reference to the drawings. However, the electrode catalyst, electrode, and battery of the present invention are not limited to the embodiments shown in the drawings.
[0014] FIG. 1 is an explanatory diagram showing a schematic diagram of an electrode catalyst structure coated with an ionic liquid according to the present invention. An electrode catalyst is generally a catalyst in which platinum fine particles 102 are supported on a carbon fine powder or porous carbon material 103 that serves as an electrode (sometimes referred to as a "Pt / C catalyst"). Pt / C catalysts are commercially available. Specific examples include "TEC10V30E" (weight ratio of about 30 wt.%) manufactured by Tanaka Kikinzoku Co., Ltd., commercially available fuel cell catalysts, and Pt-supported porous carbon catalysts (Pt supported on porous carbon materials such as "Vulcan" and "Ketjen" or mesoporous carbon (MPC)) prepared by thermal reduction, hydrogen reduction, alcohol reduction, or the like.
[0015] In the present invention, this electrode catalyst is coated with a phosphonium-type ionic liquid 103 shown below. P + (C8H 17 )3R1X - (chemical formula 1) In the chemical formula 1, C8H 17 is a linear octyl group, R1 is a linear or branched alkyl group having 1 to 18 carbon atoms, or an alicyclic alkyl group having 1 to 18 carbon atoms, and X - is the anion component.
[0016] In the examples described later, it was found that the more carbon atoms R1 in the cationic component in chemical formula 1 has, the better the results, with a carbon number of 18 being optimal. On the other hand, the number of carbon atoms in R1 is set to 18 or less because, based on the results of the examples, it is believed that a phosphonium-type ionic liquid with a carbon number of more than 18 would have an increased hydrophobicity as a physical property and would be more suitable for use, but it is difficult to synthesize and difficult to obtain in a stable manner with current technology. + (C8H 17 )3R1) is specifically P + (C8H 17 )3(C2H5)3, P + (C8H 17 )3(C4H9)3, P + (C8H 17 )3(C8H 17 )3 can be mentioned as examples.
[0017] The anion component (X -) can be used without any particular limitation as long as it is an anion exhibiting hydrophobicity, and specific examples thereof include bis(trifluoromethanesulfonyl)imide anion, triflic acid anion, bis(pentafluoroethyl)sulfonylimide anion, (fluorosulfonyl)-N-(fluoromethylsulfonyl)imide anion, nonafluorobutanesulfonic acid anion, (fluorosulfonyl)-N-(pentafluoroethylsulfonyl)imide anion, (trifluoromethylsulfonyl)-N-(nonafluorobutylsulfonyl)imide anion, bis(nonafluorobutyl-sulfonyl)imide, 2,2,2-trifluoro-N-(trifluoromethylsulfonyl)acetamide anion, and 2,2,2-(trifluoromethyl)sulfonyl-N-cyanamide anion. These anion components can be used alone or in combination of multiple components.
[0018] The method of coating the Pt / C catalyst with the phosphonium-type ionic liquid is as follows. First, a solution is prepared by mixing the phosphonium-type ionic liquid with isopropyl alcohol at a concentration that provides sufficient fluidity (preferably 10 wt% to 60 wt% by weight ratio to isopropyl alcohol). The Pt / C catalyst is mixed into this solution. At this time, since mixing in the air may cause fire, it is preferable to perform the mixing in an inert gas. The solution containing the Pt / C catalyst and the ionic liquid is ultrasonically stirred, and then the isopropyl alcohol is evaporated using an evaporator, thereby obtaining a Pt / C catalyst in which the ionic liquid is coated on the surface of the Pt / C catalyst. FIG. 1 shows a schematic diagram of the electrode catalyst coated with the phosphonium-type ionic liquid of the present invention obtained in the above process, in which minute (generally several tens of nanometers in diameter) platinum particles 102 are in contact with porous carbon powder 103, and the ionic liquid 101 is coated around the platinum particles.
[0019] Figure 2 is a diagram that illustrates how the coated Pt / C catalyst obtained in Figure 1 is present in the cathode electrode, and Figure 3 is a diagram that illustrates the structure of an FC cell (fuel cell) and where the cathode electrode shown in Figure 2 is located in the FC cell.
[0020] The coated catalytic electrode of the present invention functions as a fuel cell as follows. Oxygen diffuses from the gas diffusion layer 201 into the Pt / C catalytic portion (102, 103) coated with ionic liquid 101, and is decomposed into oxygen ions and electrons by the catalyst. The oxygen ions combine with protons (hydrogen ions) moving to the cathode side through the electrolyte membrane 304 and the polymer electrolyte membrane 202 to generate water, and the movement of electrons and protons generates an electric current. Oxygen in the air is used, and air is introduced from the air inlet 302 of the cell. The generated water and excess air are discharged to the outside of the system from the outlet 303. Hydrogen is introduced from the hydrogen inlet 305 on the anode electrode side, and excess hydrogen is discharged to the outside of the system from the hydrogen outlet 311. EXAMPLES
[0021] [Manufacturing] The Pt / C catalyst used was a commercially available product called "TEC10V30E" (weight ratio approximately 30 wt.%, manufactured by Tanaka Kikinzoku Co., Ltd.). Next, the target ionic liquid was mixed with isopropyl alcohol (weight ratio (wt%) of isopropyl alcohol: 20.0 wt%). The mixture and the Pt / C catalyst were mixed in an inert gas and ultrasonically stirred. After that, the isopropyl alcohol was evaporated using an evaporator to obtain a Pt / C catalyst with the ionic liquid coated on its surface.
[0022] The following ionic liquids were used: P + (C8H 17 )3C 18 H 37 (Hereafter referred to as P888(18)) P + (C8H 17)3CH3 (hereinafter referred to as P888(1)) P + (C8H 17 )3C9H 19 (Hereafter referred to as P888(9)) The above is an example. As a comparative example, a Pt / C catalyst coated with the following ionic liquid was also prepared. P + (C2H5)3C 18 H 37 (Hereafter, referred to as P222(18)) P + (C4H9)3C 18 H 37 (Hereafter referred to as P444(18)) In addition, in all ionic liquids, the anion is TFSI (bis(trifluoromethanesulfonyl)imide). As a reference example, a Pt / C catalyst coated with a perfluorosulfonic acid-based cation exchange membrane "Nafion" (registered trademark) (hereinafter referred to as "Nafion") was used.
[0023] 〔evaluation〕 The activity of the Pt / C catalysts with each coating was evaluated by measuring the mass activity and surface area specific activity of platinum. Mass activity and surface area specific activity were evaluated by the oxygen reduction reaction (ORR) activity evaluation method using the rotating electrode (RDE) method. In addition, durability was evaluated by the cyclic voltammetry method after applying a specified load. These evaluation methods are standard evaluation and analysis protocols created in cooperation with the Fuel Cell Commercialization Promotion Council of Japan (FCCJ) and the New Energy and Industrial Technology Development Organization (NEDO), and details are described in the "NEDO PEFC Cell Evaluation and Analysis Protocol March 2022 Edition." The results of the activity evaluation are shown in Figures 4 and 5. In addition, the results of the durability evaluation are shown in Figures 6 and 7.
[0024] In the graph of FIG. 4, the vertical axis shows the catalytic activity per surface area (Pt surface area specific activity, (B) in the figure) and the activity per Pt mass (mass activity, (A) in the figure) for P888(18) (Example), P222(18) (Comparative Example), P444(18) (Comparative Example), and Nafion of the Reference Example. 18 H 37 The longer the carbon number of the remaining three groups bonded to phosphorus, the higher the specific activity and mass activity tend to be. In addition, compared to the case where the reference example Nafion is used, it can be seen that the oxygen reduction reaction (ORR) activity is improved, that is, the efficiency as an electrode catalyst is improved.
[0025] FIG. 5 is a graph showing catalytic activity per surface area (Pt surface area specific activity) and activity per Pt mass (mass activity) on the vertical axis, similar to FIG. 4, but the results are for P888(18), P888(1), P888(9) (all of which are examples) and Nafion (Reference Example). For the examples, the three groups bonded to phosphorus are -C 18 H 37 and the remaining group that bonds to phosphorus is CH3, C9H 19 or C 18 H 37 As shown in Figure 5, in our experiments, all of the examples showed superior results in terms of mass activity and surface area specific activity compared to the reference Nafion. However, upon closer consideration, it was found that the ionic liquid coated with CH3 groups had a higher C 18 The results showed that the ionic liquid coated with the group was slightly superior in mass activity and surface area specific activity, but in all examples, the oxygen reduction reaction (ORR) activity was improved compared to the reference example, i.e., the efficiency as an electrode catalyst was improved.
[0026] The graph in FIG. 6 is a comparison of P222(18), P444(18) (the above are comparative examples), P888(18) (Examples) and the Reference Example, where the horizontal axis (C) is the number of times the load was applied, and the vertical axis (D) is the result of calculating the Pt surface area retention rate (%) measured by cyclic voltammetry after the load was applied. The higher the Pt surface area retention rate (%), that is, the smaller the rate of change from the beginning of the test (i.e., the closer the retention rate is to 100%), the higher the durability can be evaluated. As shown in FIG. 6, although there is a difference in the initial deterioration, the amount of change is small in both the Examples and the Comparative Examples after the load was applied more than 10,000 times. In the experiment we conducted this time, P888(18) showed the least initial deterioration and long-term stability (low rate of change).
[0027] In FIG. 7, the horizontal axis is the number of times the load was applied, and the vertical axis is the Pt surface area retention rate (%) calculated by cyclic voltammetry after the load was applied, as in FIG. 6, but the results are for P888(18), P888(1), P888(9) (all of which are examples) and the reference example Nafion. In the results of our experiments, P888(1) showed little initial deterioration, but the degree of deterioration increased from the middle of the experiment, and conversely, P888(18) showed greater initial deterioration than the other examples, but its stability seemed to improve as the number of tests increased. It can also be seen that all of the examples showed more stable durability than the reference example.
[0028] In this study, we evaluated ionic liquids that use a straight-chain alkyl group for R1 in chemical formula 1. However, because the thickness and characteristics of the ionic liquid layer are similar, similar trends are predicted for ionic liquids that have branched-chain alkyl groups with 1, 9, or 18 carbon atoms, or alicyclic alkyl groups with 1, 9, or 18 carbon atoms, and improvements in efficiency and durability are expected. [Industrial Applicability]
[0029] The electrode catalyst coated with the phosphonium-type ionic liquid of the present invention has higher oxygen reduction reaction activity and is more durable than the electrode catalyst coated with the conventional perfluorosulfonic acid-based cation exchange membrane, and therefore electrodes using this are expected to have great industrial applicability, particularly as a material for fuel cells for large vehicles. [Explanation of symbols]
[0030] 101 Phosphonium-type ionic liquids 102 Platinum fine particles 103 Carbon fine powder or porous carbon material 201 Gas diffusion layer 202 Polymer electrolyte membrane 203 Structure of the cathode electrode part 301 Fuel Cell Cathode Electrode of the Present Invention 302 Air (oxygen) inlet 303 Water and excess air (oxygen) outlet 304 Electrolyte membrane 305 Hydrogen inlet 306 Anode side electrode of fuel cell 307 cases 308 Gas diffusion layer of cathode electrode 309 Gas diffusion layer of anode electrode 310 Enlarged schematic diagram of the electrolyte membrane side of the cathode electrode (same as shown in Figure 2) 311 Excess hydrogen outlet (A) Mass activity (A / cm 2 ) (B) Surface area specific activity (A / g) (C) Pt surface area retention rate (%) (D) Number of cycles of the test
Claims
1. An electrode catalyst coated with a phosphonium-type ionic liquid represented by the following chemical formula 1. P + (C 8 H 17 ) 3 R 1 X - (Chemical formula 1) (In Chemical Formula 1, C 8 H 17 is a straight-chain octyl group, R 1 is a linear or branched alkyl group having 1 to 18 carbon atoms, or an alicyclic alkyl group having 1 to 18 carbon atoms; X - is the anion component.)
2. The anion component (X - ) is bis(trifluoromethanesulfonyl)imide anion, triflic acid anion, bis(pentafluoroethyl)sulfonylimide anion, (fluorosulfonyl)-N-(fluoromethylsulfonyl)imide anion, nonafluorobutanesulfonic acid anion, (fluorosulfonyl)-N-(pentafluoroethylsulfonyl)imide anion, (trifluoromethylsulfonyl)-N-(nonafluorobutylsulfonyl)imide anion, bis(nonafluorobutyl-sulfonyl)imide, 2,2,2-trifluoro-N-(trifluoromethylsulfonyl)acetamide anion or 2,2,2-(trifluoromethyl)sulfonyl-N-cyanamide anion, or is composed of a plurality of the anion components listed above. Electrocatalyst according to claim 1.
3. An electrode comprising the electrode catalyst according to claim 1.
4. A fuel cell comprising the electrode according to claim 3.
Citation Information
Patent Citations
Phosphonium ionic liquids, salts, compositions, production methods and devices formed therefrom
JP2016507855A
Cited By
Composition for forming cathode catalyst layer of polymer electrolyte fuel cell, and cathode catalyst layer
WO2026110759A1